WAR CRIMES DURING WORLD WAR II IN UKRAINIAN SCIENTIFIC AND PUBLIC DISCOURSES - ARTYMYSHYN , Yuliia; TARASENKO , Oleh (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to define the conceptual and categorical specificity of the term “war crime”, its application to the studied violations of the international law as well as to outline a thematic and contextual framework for studying the war crimes issues in Ukraine during World War II. The research methodology is based on a complex of general scientific (analysis, synthesis, induction and deduction) and special (historical and legal, historical and typological, historical and systemic, retrospective) methods of scientific research. The scientific novelty consists in the process of determining the concepts “war crime” and “military crime” in the international humanitarian law, and the Ukrainian interpretation of these concepts. There has been outlined the discourse of the study on the war crimes in the Ukrainian humanitarian studies comprehensively. There have been covered diverse manifestations of mass violence and political terror in the context of studying socio-political aspects of World War II. Conclusions. There were published numerous studies of a generalizing nature regarding World War II in Ukrainian historiography during the 1990s and the first half of the 2000s. There were also considered the information reports, research reports among the issues, which covered violations of the norms and customs of war, extreme violence against civilian population, prisoners of war. However, there has been carried out a more systematic study on the issues of the war crimes on the Ukrainian territory since the mid-2000s. There were brought out important studies on the policy of mass violence and terror of the Nazis during the occupation in 1941 – 1945 by O. Lysenko, V. Vasyliyev, collective studies edited by H. Boriak, V. Smolii, etc. The above-mentioned issues were discussed in more detail, as well as a regional cross-section of the repressive practices (including ideological reasons) against civilians, as well as murdering of prisoners of war, forced mobilization, in the studies by V. Shaikan, M. Shevchenko, S. Halchak, V. Levykin, T. Pastushenko, etc. The research on the “Extraordinary State Commission for Determination and Investigation on Atrocities of the German-Fascist Invaders and their Accomplices” in Ukrainian historical science, a regional cross-section of the work of this commission is considered to be another thematic study. Although, there is growing interest in the issues on implementing the norms of the international criminal law in modern Ukrainian legislation in public, popular scientific discourse, as well as in jurisprudence, which are relevant to the war crimes issue, the formation of an evidentiary base for the future prosecution of the Russian Federation for the atrocities committed in Ukraine since 2014, and mainly within the framework of the full-scale armed aggression. Key words: war crime, World War II, Nazi occupation regime, civilian population, prisoners of war, mass violence, the Russo-Ukrainian War.